2010
DOI: 10.1002/ange.200906001
|View full text |Cite
|
Sign up to set email alerts
|

Von der Entdeckung bis zur Anwendung: 50 Jahre Vinylcyclopropan‐Cyclopenten‐Umlagerung und ihre Bedeutung in der Naturstoffsynthese

Abstract: Ein Klassiker mit Charme: Die historischen Ursprünge und der heutige Stand der Vinylcyclopropan‐Cyclopenten‐Umlagerung sowie die entsprechenden Umwandlungen von Heteroanaloga (siehe Schema) werden anhand der Methodenentwicklung und der Naturstoffsynthese geschildert. Einige wichtige Ereignisse, die vor etwa 30 bis 40 Jahren starken Einfluss auf das Forschungsprogramm der Autoren hatten, werden aus persönlicher Erinnerung erzählt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…For example, vinylcyclopropane-cyclopentene rearrangement is well-known to require usually heating at 300-600 8C or use of photolysis. [41] Oppositely, we showed that alkenylcyclopropanes 50 with acceptor groups at the vicinal position undergo Lewis acid-induced isomerization to cyclopentenes 51 under mild reaction conditions. A broad scope of substrates containing diverse acceptors successfully underwent this rearrangement.…”
Section: Isomerization Of Donor-acceptor Cyclopropanesmentioning
confidence: 92%
“…For example, vinylcyclopropane-cyclopentene rearrangement is well-known to require usually heating at 300-600 8C or use of photolysis. [41] Oppositely, we showed that alkenylcyclopropanes 50 with acceptor groups at the vicinal position undergo Lewis acid-induced isomerization to cyclopentenes 51 under mild reaction conditions. A broad scope of substrates containing diverse acceptors successfully underwent this rearrangement.…”
Section: Isomerization Of Donor-acceptor Cyclopropanesmentioning
confidence: 92%
“…[19] To the best of our knowledge, neither gold-promoted nor enantioselective variants of these reactions have been reported so far. [20] Both 17 and 18 have been obtained in ! If R is H, the reaction affords the [4.1.0]bicycloheptene 17, whereas the reaction affords the rearranged product 18 if R is a phenyl group.…”
Section: Methodsmentioning
confidence: 99%
“…The vinylcyclopropane-cyclopentene rearrangement leading to 18 takes place at room temperature, in a reaction that is likely to be promoted by gold itself. [20] Both 17 and 18 have been obtained in ! 85 % ee.…”
Section: Methodsmentioning
confidence: 99%
“…We speculate that the reactions proceed through a sigmatropic rearrangement of the vinylcyclopropane and divinylcyclopropane intermediates to form 3 and 4 , respectively. The vinylcyclopropane rearrangement to cyclopentene17,18 and divinylcyclopropane to cycloheptadiene19 have been extensively applied to the syntheses of complex natural products and important organic molecules. This article describes the application of these classic rearrangements of indoles to the synthesis of spiro[cyclopent[3]ene‐1,3′‐indole] derivatives through a thermal [1,3]‐sigmatropic shift and tetrahydrocyclohepta[ b ]indole derivatives through a thermal [3,3]‐sigmatropic shift.…”
Section: Introductionmentioning
confidence: 99%